Advances on Digital Television and Wireless Multimedia Communications 9th International Forum on Digital TV and Wireless Multimedia Communication, IFTC 2012, Shanghai, China, November 9-10, 2012. Proceedings - Zhang, Wenjun; Yang, Xiaokang; Xu, Zhixiang; An, Ping.; Liu, Qizhen; Lu, Yue.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 9th International Forum on Digital TV and Wireless Multimedia Communication, IFTC 2012, Shanghai, China, November. The 69 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on image processing and pattern recognition; image and video analysis; image quality assessment; text image and speech processing; content retrieval and security; source coding; multimedia communication; new advances in broadband multimedia; human computer interface; 3D video.
Image processing and pattern recognition -- Image and video analysis -- Image quality assessment -- Text image and speech processing -- Content retrieval and security -- Source coding -- Multimedia communication -- New advances in broadband multimedia -- Human computer interface -- 3D video.
Keywords: Computer science; Information systems; Information storage and retrieval systems; Multimedia systems; Computer vision; Optical pattern recognition; Computer Science; Image Processing and Computer Vision; Pattern Recognition; Multimedia Information Systems; Information Storage and Retrieval; Information Systems and Communication Service